Prenos toplote v toku ledene brozge - Šarlah, Alen (Strojniški vestnik, 2005)
An ice slurry is a harmless substance that can be used in various cooling systems because of its good thermal properties. Until recently, systems with ice slurries were limited to food processing, where conventional, harmful refrigerants are not allowed. The rapid development of such systems and the many innovations in refrigeration have paved the way for ice-slurry systems tobe used in other areas, e.g., district cooling. However, a lot of research remains to be done, especially experimental work. This paper deals with the research results from heat transfer in an ice-slurry flow within a rectangular channel. First, the basics of heat transfer in an ice slurry are explained. Next the experiment to determine the intensity of the heat transfer is explained. Later, the results are explained, and together with the results of some other experiments, shown in diagrams for comparison. In the second part of the paper a numerical program is described: this was used to compare numerical and experimental data. Finally, conclusions from the comparison between the experimental and numerical results are given and discussed.
Keywords: brozga ledena; prenos toplote; profili temperaturni; programi numerični; led; light-emitting diode; porazdelitev temperature